北海道知床らうす簡易取水施設から採集した付着珪藻 (海洋深層水利用研究会, 2008)
北海道知床らうす簡易取水施設 (羅臼町) で, 深層水 (取水深度218m) をかけ流している屋内実験水槽内に出現した付着珪藻類を2004年12月から1年間調べ, 光学および走査型電子顕微鏡で観察し, 7属11種の出現を確かめた.主要種は, Achnanthes sp., Amphora sp., Cocconeis pinnata, Cocconeis sp.1, Naicula sp.1, Nitzschia tabicolaおよびTryblionella sibulaで, このうち.Amphora sp., Cocconeis sp.1, Navicula sp.1およびNitzschia tubicolaは高頻度で出現した.これらの種類は他の深層水施設の報告に記録がなく, 本深層水に特徴的に出現した可能性が高い.本研究の結果は, 深層水に対する珪藻の生物指標的アプローチの可能性を示唆しており, 今後各地の深層水施設に出現する珪藻の種組成とその動態を調査することにより, 海洋深層水の新たな特性の発見が期待されると結論した. The present study identified the characteristic attached diatoms derived from Shiretoko Rausu Deep Seawater (DSW) pumped from a depth of 218 m in Okhotsk Sea. Diatom samples were collected from a DSW tank seasonally from December 2004 to December 2005 and identified using light and scanning electron microscopy. A totalof 11 species in 7 genera were recorded. The most common taxa encountered were Amphora sp. and Cocconeis sp. 1. Amphora sp. was dominant from winter to spring and thereafter decreased gradually, whereas Cocconeis pinnata and Cocconeis sp. 1 increased from spring to summer. Navicula sp. 1 and Nitzschia tubicola were common but decreased in summer. Tabularia investiens was in constant occurrence. Theoverall attached diatom flora in Shiretoko Rausu DSW was different from those previously observed by the authors in other DSW facilities (Namerikawa, Nyuuzen and Muroto) in Japan. In the present paper, morphologic and taxonomic comments were given for the above 5 species as well as the other two species, Achnanthes sp. and Tryblionella sibula. 公開日: 2010-06-28 20580197 journal article